A comparison of infarct mass by cardiac magnetic resonance and real time myocardial perfusion echocardiography as predictors of major adverse cardiac events following reperfusion for ST elevation myocardial infarction. Issue 10 (21st August 2016) - Lenz, Charles J; Abdelmoneim, Sahar S; Anavekar, Nandan S; Foley, Thomas A; Nhola, Lara F; Huang, Runqing; Oh, Jae K; Mulvagh, Sharon L
Abstract : Purpose: Infarct mass as assessed by myocardial‐delayed enhancement imaging on cardiac magnetic resonance (CMR) and myocardial blood flow as assessed by real time myocardial perfusion echocardiography (RT‐MPE) have been shown to predict adverse events following ST elevation myocardial infarction (STEMI). There has been no published comparison of quantitative assessment using these modalities as predictors of clinical outcomes to date. We compared RT‐MPE with CMR for prediction of cardiac events in reperfused STEMI patients. Materials and Methods: Consecutive STEMI patients with early reperfusion were studied. RT‐MPE and CMR were performed. Perfusion score indices (PSIRT ‐ MPE and PSICMR ) were calculated [sum of segmental perfusion scores/number of segments]. CMR infarct mass (g) and RT‐MPE myocardial blood flow (MBF dB/s) were quantified. Patients were followed for cardiac events (death, nonfatal MI, revascularization, angina, and heart failure). Results: All 27 patients (age 62±14; follow‐up 3.5±2.6 years) had thrombolysis in myocardial infarction (TIMI) grade 3 flow of infarct vessel. Cardiac events occurred in 17 (63%). Cardiac event patients had higher PSIRT ‐ MPE, PSICMR, infarct mass, and lower MBF. PSIRT ‐ MPE cutoff of 0.3 had an AUC of 0.856 (82% sensitivity, 70% specificity), while a PSICMR cutoff of 0.2 had an AUC of 0.765 (76% sensitivity, 60% specificity). Infarct mass and MBF were independent predictors of cardiac events after adjusting for risk factors (hazard ratios: 20.9 [95% CI 1.8–256] P =.02 and 8.1 [95% CI 1.5–78] P =.01, respectively). Conclusions: Quantitative RT‐MPE performed comparably to CMR for prediction of MACE in STEMI patients supporting a prognostic role for this noninvasive, bedside imaging method.